EXPLORING THE CONTRIBUTION OF COLLABORATION BETWEEN SCHOOL COUNSELORS AND PARENTS IN AN EFFORTS TO IMPROVE STUDENTS' MOTIVATION AND LEARNING ACHIEVEMENT IN THE SCHOOL ENVIRONMENT - Inneke Leeuwanda s; Mudhar Mudhar (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to examine the contribution of collaboration between school counselors and parents in enhancing students' motivation and academic achievement. The phenomenon under investigation stems from the still low level of parental involvement in education and the not yet optimal role of school counselors as mediators of school–family partnerships. This study employs a qualitative approach with a case study design. Data were collected through in-depth interviews, non-participant observation, and documentation studies involving school counselors, parents, and students in two secondary education institutions. Participants were selected purposively based on their direct involvement in guidance and counseling services. The results of the thematic analysis indicate that collaboration between school counselors and parents contributes positively to the improvement of students' learning motivation through consistent communication, emotional support, and the alignment of learning assistance at school and at home. However, this collaboration remains situational and has not been systematically structured, resulting in less optimal and sustainable impacts on students' academic achievement. The findings of this study enrich the theoretical understanding of School–Family–Community Partnerships by emphasizing the strategic role of school counselors as professional mediators. Practically, these results imply the need to develop a more planned and preventive counselor–parent collaboration model supported by school policies. Future research is recommended to examine this collaboration using quantitative or mixed-methods approaches in order to obtain a more comprehensive understanding.